Comparison of Assessment Methods for Fallopian Tubal Patency and Peritubal Adhesion Between Transvaginal 4‐Dimensional Hysterosalpingo‐Contrast Sonography and Laparoscopic Chromopertubation. (2nd February 2017) - He, Yanni; Ma, Xiaohui; Xu, Jingjiao; Li, Sushu; Wu, Haorong; Liu, Qiuxiang; Kong, Linghong; Luo, Juan; Liu, Hongmei
Abstract : Objectives: The purpose of this study was to compare transvaginal 4‐dimensional hysterosalpingo‐contrast sonography with laparoscopic chromopertubation and evaluate the former's clinical value in assessing fallopian tubal patency and peritubal adhesion. Methods: Fifty‐six patients visiting infertility clinics were included in the study and underwent surgery by their own choice in 1 month. In total, 112 fallopian tubes were assessed. Twenty‐five were primarily infertile, and the rest were secondarily infertile. Laparoscopic chromopertubation was taken as the reference standard. Results: In a comparison of fallopian tubal patency between transvaginal hysterosalpingo‐contrast sonography and laparoscopic chromopertubation, the sensitivity, specify, positive predictive value, and negative predictive value of hysterosalpingo‐contrast sonography for diagnosing blocked fallopian tubes were 88.4%, 85.2%, 90.5%, and 82.1% respectively. In a comparison of spray at the fimbrial end between the no–peritubal adhesion and peritubal adhesion groups, the spray score at the fimbrial end in the no–peritubal adhesion group was significantly lower than that in the peritubal adhesion group. In a comparison of periovarian diffusion between the no–peritubal adhesion and peritubal adhesion groups, the periovarian diffusion score in the no–peritubal adhesion group was significantly lower than that in the peritubal adhesion group. In a comparison of periovarian diffusion between the patent‐tube and blocked groups confirmed by chromopertubation, the periovarian diffusion score in the patent group was significantly lower than that in the blocked group. Conclusions: Transvaginal hysterosalpingo‐contrast sonography is a method with high sensitivity and specificity for screening fallopian tubal patency and peritubal adhesion.